Critical analysis of cases of endometrial carcinoma of the uterine corpus incidentally diagnosed after incomplete surgery for other indications. Three case reports and a review of the literature - Gajewska, Małgorzata; Wielgoś, Mirosław; Panek, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2014)
Incidental diagnosis of endometrial carcinoma after the operation for presumed benign disease is rare. At present, there are no recognized guidelines on optimal management of uterine malignancy diagnosed after incomplete surgery for other indications and the reported experience is limited. Although the risk of histological diagnosis of endometrial carcinoma in the uterus removed for pre-operatively diagnosed benign disease is very low, one should always bear in mind that it may indeed occur. Omission of certain diagnostic procedures prior to hysterectomy may result in incidental finding of a malignancy at or after surgery, even when preoperative imaging studies reveal benign disease. Many centres develop their own strategies, although in most cases the adnexa and cervix are removed and thorough exploration of the abdominal cavity is performed. Also, in view of the technical difficulties involved in removing the uterus and adnexa via the vagina and a potential high risk of cancer either developing in the cervical stump or disseminated from inadvertently morcellated uterine fragments, one should carefully consider the potential benefits and risks of supracervical hysterectomy. We present three patients with endometrial carcinoma diagnosed after hysterectomy, who subsequently underwent completion surgery. A review of the literature follows, which presents opinions from international centres.